On the Li Intercalation Kinetics in Tree‐like WO3 Electrodes and Their Implementation in Fast Switchable Electrochromic Devices. Issue 11 (21st August 2015) - Giannuzzi, Roberto; Balandeh, Mehrdad; Mezzetti, Alessandro; Meda, Laura; Pattathil, Praveen; Gigli, Giuseppe; Di Fonzo, Fabio; Manca, Michele
Abstract : Fast switchable electrochromic devices can be realized through the implementation of engineered quasi‐1D WO3 nanostructures. Three different batches of WO3 working electrodes have been fabricated by controlling the self‐assembly process of the evaporating WO3 clusters to build up a forest of high aspect‐ratio tree‐like nanostructures that conjugate the peculiar features of 1D nanoarchitectures (which are characterized by relatively fast electron transport) and those ones of isotropic mesoporous films (which are characterized by relatively high surface area). Their unique morphological prerogatives have been favorably exploited to achieve good coloration efficiency (65 cm 2 C −1 at 660 nm) and exceptionally short coloration time (<1 s at an applied voltage of 1.3 V). Both electrochemical impedance spectroscopy and galvanostatic intermittent titration analyses have been carried out to elucidate the impact of their nanoscale architecture on the Li insertion kinetics. Crystalline and amorphous building blocks have been tested while keeping the same nanoarchitecture, which exhibited two different electrochromic behaviors. Abstract : Hyperbranched high aspect‐ratio WO3 nanostructures are a beneficial architecture for high‐performance electrochromic electrodes as they offer a superhighway for electron and ion transport as well as enduring large volume changes which accommodate intensive lattice strain. An exhaustive electrochemical analysis elucidates the correlation between the nanoscale morphology and Li + intercalation kinetics.